Sampling and choosing cases in qualitative research : a realist approach - Emmel, Nick (London : SAGE, 2013)
Helping students to become familiar with various sampling techniques and how to make empirical and theoretical claims from the cases they choose, this text introduces widely used sampling methodologies and identifies key theoretical assumptions.
Machine generated contents note: pt. One The cases -- 1.Theoretical sampling -- 2.Purposeful sampling -- 3.Theoretical or purposive sampling -- pt. Two Choosing cases -- 4.The basics of realist sampling -- 5.Purposive work in a realist sampling strategy -- 6.Purposefully choosing cases -- 7.Interpretation and explanation -- 8.Sample size -- 9.Choosing cases in qualitative research -- References.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Qualitative research -- Methodology; Society